Pilot evaluation of parental and professional views regarding consent in neonatal medicine by telephone interviews and questionnaires. Issue 1 (1st November 2017) - Vasu, Vimal
Abstract : Objective: The objectives of the study were to determine (1) parental and professional views regarding the type of consent required for common neonatal interventions and (2) whether there has been a change in professional understanding regarding the requirements of consent since the last UK survey in 2003. Design: Cohort study of (1) parents of babies admitted to a single-centre tertiary neonatal unit and (2) healthcare professionals. Methods: The views of 8 parents of former neonatal patients and 69 neonatal professionals were sought using online and telephone survey methodology regarding 20 neonatal interventions and whether implied consent, explicit verbal consent or explicit written consent should be obtained. Results: Agreement, defined as both parental and professional consensus on the type of consent required, was present in 12/20 of the interventions. Comparison between professional views in 2003 demonstrated a change regarding type of consent for 50% of interventions with a shift towards obtaining explicit written consent certain treatments. Conclusions: The study indicates areas of consensus that exist between parents and professionals regarding consent for common neonatal interventions and a change in professional views regarding consent since the last UK survey in 2003. These data might help inform the development of national guidance for how professionals should obtain consent in neonatology.